Implication of vasopressin receptor genes (AVPR1A and AVPR1B) in the susceptibility to polycystic ovary syndrome - Pruthvi Goparaju; Claudia Gragnoli (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex heterogenous disorder manifesting with various reproductive, endocrine, and metabolic derangements such as insulin resistance and hyperglycemia. The arginine vasopressin peptide (AVP), also called or antidiuretic hormone (ADH), modulates metabolic functions such as glucose hemostasis, insulin sensitivity, and lipid metabolism via binding to two central and peripheral receptors (AVPR1A and AVPR1B). In the present study, we aimed to detect whether the AVPR1A and AVPR1B genes confer risk for PCOS. Methods In peninsular Italian families, we tested 7 variants in the AVPR1B gene and 2 variants in the AVPR1A gene via Pseudomarker for linkage and linkage joint to association (i.e.., linkage disequilibrium) with PCOS. Results We identified two risk variants in each gene, significantly associated with the risk of PCOS. Conclusion To the best of our knowledge, this is the first study to report risk variants in AVPR1A and AVPR1B genes in association with PCOS. However, replication in other ethnic groups as well as functional studies are needed to confirm these results.